1993
DOI: 10.1063/1.464670
|View full text |Cite
|
Sign up to set email alerts
|

A combined theoretical and experimental study of the dissociation of benzene cation

Abstract: Variational Rice–Ramsperger–Kassel–Marcus (RRKM) theory calculations of the energy and angular momentum dependence of the rate constant for the dissociation of C6H6+ into C6H5+ and an H atom are reported. In these variational calculations both the definition of the reaction coordinate and its value are independently optimized. A model potential-energy surface which interpolates between a Morse potential at short range and an ion-induced dipole potential at long range is employed in these variational calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 68 publications
5
54
0
Order By: Relevance
“…Some of these benzene cation dissociation channels have been found in the previous studies. [21][22][23][24][25] The study of photolysis laser power dependence in the region of 0.5-10 mJ/cm 2 showed that ions of the disklike image result from one photon absorption. The results of the experiments can be described with the following reactions.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these benzene cation dissociation channels have been found in the previous studies. [21][22][23][24][25] The study of photolysis laser power dependence in the region of 0.5-10 mJ/cm 2 showed that ions of the disklike image result from one photon absorption. The results of the experiments can be described with the following reactions.…”
Section: Methodsmentioning
confidence: 99%
“…Molecules in the CIT-RETOF mass spectrometer were cooled in a supersonic jet. 44 Ions in the FT-ICR experiments 44,82 had a thermal energy distribution leading to an internal energy width of about 0.13 eV. The experimental results, summarized in Figure 2, 44 are due to the two experimental groups: Neusser's group in Munich 44 (filled symbols) who used a TOF instrument and Klippenstein and Dunbar's group 82 (open symbols) who used FT-ICR.…”
mentioning
confidence: 98%
“…However, most gas‐phase reactivity studies involving the naphthyl cation have largely ignored possible implications of the different spin states20, 21 or simply assumed both states to occur 15. Moreover, H‐atom abstraction (HAA) from the benzene cation was first assumed to produce the (higher‐energy) triplet phenyl cation,27 but later studies suggested that an intersystem crossing occurs on the dissociation pathway, rapidly converting the system to the (lower‐energy) singlet state 6. Spin isomerization between singlet and triplet states has also been suggested to occur rapidly for a series of para ‐substituted phenyl cations, p‐ X‐C 6 H 4 + , such that the lower‐energy state is always found independent of how the species was formed 28.…”
Section: Methodsmentioning
confidence: 99%